L’utre et le neutre : la binarité et l’altérité - Daniel Elmiger (Glad!)
Unlike Latin, which still had three grammatical genders, French now has only two, the feminine and the masculine. While certain (semantic or formal) neutralisation strategies are possible, the neuter as a grammatical gender is absent – unless it is recreated, which would require a profound restructuring of French morphology. Nevertheless, the discourse around the neuter allows us to better conceive of the uter, namely the binarity inherent in language, which can prevent us from considering non-binarity.